2009
DOI: 10.1074/jbc.m806457200
|View full text |Cite|
|
Sign up to set email alerts
|

KSR1 Is Required for Cell Cycle Reinitiation Following DNA Damage

Abstract: ؊/؊ cells, as determined by resolution of ␥-H2AX-containing foci. These data indicate that cell cycle reinitiation is not actively signaled in the absence of KSR1, even when DNA damage has been resolved. These data reveal a specific role for the molecular scaffold KSR1 and KSR1-mediated ERK signaling in the cellular response to DNA interstrand cross-links.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Metastasis suppressor Nm23-H1 can bind directly to KSR1 and phosphorylate KSR1 at Ser 392 , and can therefore facilitate its degradation as a result of decreased ERK activation [35,36]. KSR1 was also required for cell-cycle reinitiation in response to DNA-damage agents such as mitomycin C [37]. Additionally, through modulation of PGC1α [PPARγ (peroxisome-proliferatoractivated receptor γ ) co-activator 1α] and ERRα (oestrogenrelated receptor α), KSR1 was demonstrated to induce oncogenic Ras-dependent anchorage-independent growth [38].…”
Section: The Roles Of Ksr1 In Various Biological Processes Ksr1 In Camentioning
confidence: 99%
“…Metastasis suppressor Nm23-H1 can bind directly to KSR1 and phosphorylate KSR1 at Ser 392 , and can therefore facilitate its degradation as a result of decreased ERK activation [35,36]. KSR1 was also required for cell-cycle reinitiation in response to DNA-damage agents such as mitomycin C [37]. Additionally, through modulation of PGC1α [PPARγ (peroxisome-proliferatoractivated receptor γ ) co-activator 1α] and ERRα (oestrogenrelated receptor α), KSR1 was demonstrated to induce oncogenic Ras-dependent anchorage-independent growth [38].…”
Section: The Roles Of Ksr1 In Various Biological Processes Ksr1 In Camentioning
confidence: 99%
“…KSR1 is an essential scaffold protein of the Ras/Raf/MAPK cascade that facilitates the activation of ERK (3). Studies have shown that the expression of KSR1 is upregulated in many types of cancer and is required for cell proliferation, apoptosis and cell-cycle reinitiation (4)(5)(6). Moreover, KSR1 was confirmed to contribute to tumorigenesis through the MAPK cascade in a mouse model (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Different scaffold proteins for the MAPK pathway regulate intracellular signaling by providing spatial and temporal specificity 30. One example is kinase suppressor of Ras, which binds Raf, Mek and Erk at the plasma membrane and has been described as a regulator of cell cycle reinitiation following DNA damage 31, cellular proliferation and transformation 32. We have shown that the localization of another MAPK scaffold complex with Mek partner 1 (MP1 or MAPBP) and its adaptor p14 (MAPBPIP) to late endosomes is required for the regulation of late endosomal traffic and proliferation 33, 34.…”
Section: Discussionmentioning
confidence: 99%